2013
DOI: 10.1136/amiajnl-2012-001241
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in medication errors in hospitals due to adoption of computerized provider order entry systems

Abstract: ObjectiveMedication errors in hospitals are common, expensive, and sometimes harmful to patients. This study's objective was to derive a nationally representative estimate of medication error reduction in hospitals attributable to electronic prescribing through computerized provider order entry (CPOE) systems.Materials and methodsWe conducted a systematic literature review and applied random-effects meta-analytic techniques to derive a summary estimate of the effect of CPOE on medication errors. This pooled es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
207
2
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(220 citation statements)
references
References 24 publications
8
207
2
3
Order By: Relevance
“…4,34 Overall, we found rudeness explained 52% of the variance in diagnostic performance and 43% of the variance in procedural performance. In comparison, recent meta-analyses found that structural factors such as the presence/absence of computerized order entry systems explained just 12.5% of the variance in medication error 38 and chronic sleep loss explained just 23% of the variance in physician clinical performance. 39 We concluded from these findings that greater attention should be paid to dayto-day social interaction as a critical risk factor for iatrogenesis, and that in taking steps to enhance patient safety, policy makers should begin to consider the role played by the subtle and seemingly benign verbal aggression to which medical professionals are subjected on a routine basis.…”
Section: Discussionmentioning
confidence: 99%
“…4,34 Overall, we found rudeness explained 52% of the variance in diagnostic performance and 43% of the variance in procedural performance. In comparison, recent meta-analyses found that structural factors such as the presence/absence of computerized order entry systems explained just 12.5% of the variance in medication error 38 and chronic sleep loss explained just 23% of the variance in physician clinical performance. 39 We concluded from these findings that greater attention should be paid to dayto-day social interaction as a critical risk factor for iatrogenesis, and that in taking steps to enhance patient safety, policy makers should begin to consider the role played by the subtle and seemingly benign verbal aggression to which medical professionals are subjected on a routine basis.…”
Section: Discussionmentioning
confidence: 99%
“…It is nearly impossible, even for pharmacists with advanced training, to maintain a sufficient degree of competency to prevent adverse events through drug interactions. The availability of electronic user interfaces during dynamic data documentation combats this weakness in health care and allows for automation of alert messages in order to reduce medication error, 22,33 as well as errors with order entry in general. However, with the rising number of alert messages during the dynamic electronic documentation process, we run the risk of ''alert fatigue'' among care providers.…”
Section: Prevention Of Medical Errormentioning
confidence: 99%
“…Only 2 of the major objectives of the documentation process are reviewed here as examples: (1) the improvement of interprovider communication, and (2) the prevention of medical error. These objectives were selected because they are 2 of the most commonly cited goals for medical data capture, [21][22][23] and they also are high-priority targets for quality improvement, since the outcomes achieved can be quantitatively measured.…”
Section: Benefits and Weaknesses Of Clinical Documentationmentioning
confidence: 99%
“…An example of improved medication safety has been the use of computer order entry that removed medication abbreviations for physician orders. This has decreased many medication mix-ups that had resulted from commonly used medication abbreviations [6]. However, it is worth noting that in complex systems, a new technology that helps reduce errors in one domain may cause new types of errors in other domains.…”
Section: Understanding Complexity and Improving The Environment Of Carementioning
confidence: 99%